Efficacy and safety of belantamab-mafodotin in triple-refractory multiple myeloma patients: A multicentric real-life experience - Iula, Rossella; De Novellis, Danilo; Trastulli, Fabio; Della Pepa, Roberta; Fontana, Raffaele; Carobene, Angela; Di Perna, Maria; D’Ambrosio, Alessandro; Romano, Martina; Leone, Aldo; De Fazio, Laura; Fiumarella, Alfonso; et al. (Frontiers in Oncology, 2022)
Belantamab-mafodotin is an innovative and selective treatment for multi-refractory/relapsed multiple myeloma (MM) patients; however, available real-life experiences on efficacy and safety are limited. In this real-world multicentric retrospective study, we enrolled 28 MM patients treated in four Hematology units of Campania region, Italy, who received a median of six treatment lines prior to belantamab-mafodotin. The overall response rate (ORR) was 40% (complete remission, CR, 11%; very good partial remission, VGPR, 11%; and partial remission, PR, 18%), with a median progression-free survival (PFS) and overall survival (OS) of 3 and 8 months, respectively. One of the most frequent drug-related adverse events was keratopathy observed in nine (32%) patients, leading to therapy discontinuation in only three (11%) of them. Moreover, 22 out of 28 total patients who were treated with at least two administrations achieved an ORR of 50% (CR, 14%; VGPR, 14%; and PR, 22%) with a median PFS and OS of 5 and 11 months, respectively. In conclusion, our multicentric study confirmed efficacy and safety of belantamab-mafodotin in triple-refractory MM patients even in the real-life setting.